Lithium-sodium alloy negative electrode material capable of inhibiting growth of lithium dendrites and application of lithium-sodium alloy negative electrode material in preparation of all-solid-state lithium battery

By using a specific ratio of lithium sodium alloy and sulfide solid electrolyte, a protective layer containing sodium sulfide is generated, which solves the problem of low cycle life of lithium-ion batteries under high ion conductivity conditions, and achieves high energy density, low cost and excellent Take into account the stability of cycles.

CN119481025APending Publication Date: 2025-02-18江苏兴杰固邦能源科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410642180.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-04-03
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

When using sulfide solid electrolytes with high ionic conductivity, existing lithium-ion batteries are difficult to have high energy density, low cost and excellent cycle stability, especially due to the low cycle life of the battery due to the growth of lithium dendrites.

Method used

Using a specific ratio of lithium sodium alloy as the negative electrode material, the preparation method includes making the lithium sodium alloy into a matrix with the dominant crystal surface as (200) crystal surface, and contacting the sulfide solid electrolyte under pressurized conditions to produce sodium sulfide-containing to inhibit the growth of lithium dendrites.

Benefits of technology

The growth of lithium dendrites is significantly inhibited, the cycle stability of lithium batteries is improved, while maintaining high capacity density and reducing preparation costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481025A_ABST
    Figure CN119481025A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium-sodium alloy negative electrode material capable of inhibiting growth of lithium dendrites and application of the lithium-sodium alloy negative electrode material in preparation of an all-solid-state lithium battery. The lithium-sodium alloy negative electrode material comprises a lithium-sodium alloy matrix, and the dominant crystal face of the lithium-sodium alloy matrix is a (200) crystal face; wherein in the lithium-sodium alloy negative electrode material, the sodium accounts for 65%-99% by mass, and the lithium accounts for 0.05%-34% by mass; practice shows that when the lithium-sodium alloy negative electrode material is applied to an all-solid-state lithium battery taking sulfide solid electrolyte as a solid electrolyte material, the growth of lithium dendrites can be remarkably inhibited, the cycling stability of the lithium battery is improved, and the lithium-sodium alloy negative electrode material also has excellent capacity density on the basis of low preparation cost and light weight; the problem that in the prior art, a user loses others is solved.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention is a divisional application of a Chinese invention patent application with an application date of April 3, 2024, application number 2024103991067, and name “A lithium-sodium alloy negative electrode material, its preparation method and application”. Technical Field

[0002] The present invention relates to the field of solid-state batteries, in particular to lithium-ion batteries, and specifically to a lithium-sodium alloy negative electrode material capable of inhibiting the growth of lithium dendrites and its application in the preparation of an all-solid-state lithium battery. Background Art

[0003] Studies have shown that sulfide solid electrolytes have excellent mechanical ductility and high ionic conductivity comparable to liquid electrolytes, making them a technical route with excellent prospects. Pure lithium metal has a very high specific capacity and a very low electrochemical potential, and is theoretically the most ideal negative electrode material. However, due to the strong reactivity of lithium metal and the easy growth of dendrites, the battery cycle life is low; especially for sulfide solid electrolytes with high ionic conductivity, pure lithium metal reacts strongly with it, and it is difficult to complete more than 10 cycles under normal conditions. The current conventional method is to add high atomic number precious metals such as silver, indium, and bismuth to the negative electrode. Although this method can effectively improve stability, it significantly increases the cost of the negative electrode and affects the capacity density of the negative electrode to a certain extent. There is an obvious problem of losing one thing while gaining another, and it is difficult to have high energy density, low cost, excellent cycle stability and other properties. Summary of the invention

[0004] The purpose of the present invention is to overcome one or more deficiencies in the prior art and provide an improved lithium-sodium alloy negative electrode material. The lithium-sodium alloy negative electrode material is applied to an all-solid-state lithium battery using a sulfide solid electrolyte as a solid electrolyte material, which can significantly inhibit the growth of lithium dendrites and improve the cycle stability of the lithium battery. It also has excellent capacity density on the basis of low preparation cost and light weight, thus overcoming the problem of neglecting one thing while focusing on another in the prior art.

[0005] The present invention also provides an application of the above-mentioned lithium-sodium alloy negative electrode material in the preparation of an all-solid-state lithium battery.

[0006] In order to achieve the above object, a technical solution adopted by the present invention is:

[0007] A lithium-sodium alloy negative electrode material, comprising a lithium-sodium alloy matrix, wherein the dominant crystal plane of the lithium-sodium alloy matrix is ​​a (200) crystal plane; wherein, in terms of mass percentage, sodium accounts for 65%-99% and lithium accounts for 0.05%-34% of the lithium-sodium alloy negative electrode material.

[0008] According to some preferred aspects of the present invention, in the lithium-sodium alloy negative electrode material, sodium accounts for more than 70% and lithium accounts for less than 30% by mass percentage.

[0009] Furthermore, in terms of mass percentage, in the lithium-sodium alloy negative electrode material, sodium accounts for 80%-95% and lithium accounts for 4%-19%.

[0010] Furthermore, in terms of mass percentage, in the lithium-sodium alloy negative electrode material, sodium accounts for 85%-95% and lithium accounts for 4%-15%.

[0011] According to some preferred aspects of the present invention, the lithium-sodium alloy negative electrode material further includes a protective layer formed on the lithium-sodium alloy substrate; wherein the protective layer contains at least 30% by mass of sodium sulfide.

[0012] Furthermore, in terms of mass percentage, sulfur accounts for 0.05%-2% in the lithium-sodium alloy negative electrode material.

[0013] In some embodiments of the present invention, the lithium sodium alloy negative electrode material further comprises, by mass percentage, 0.001%-0.5% phosphorus, 0.001%-0.5% chlorine and 0.001%-0.5% oxygen.

[0014] In some embodiments of the present invention, the protective layer further comprises lithium sulfide.

[0015] Furthermore, in some embodiments of the present invention, the protective layer also contains sodium phosphide and / or sodium chloride.

[0016] Another technical solution provided by the present invention is a method for preparing a lithium-sodium alloy negative electrode material, the preparation method comprising:

[0017] The lithium-sodium alloy is made into a lithium-sodium alloy matrix whose dominant crystal plane is the (200) crystal plane; wherein, in the lithium-sodium alloy, sodium accounts for 65%-99% and lithium accounts for 1%-35% in terms of mass percentage.

[0018] According to some preferred and specific aspects of the present invention, the lithium-sodium alloy is prepared by the following method: melting lithium metal and sodium metal, mixing to form a solid solution, and cooling.

[0019] According to some preferred aspects of the present invention, the melting temperature is controlled at 200-400°C.

[0020] In some embodiments of the present invention, the thickness of the lithium sodium alloy is controlled to be 30-1000 μm.

[0021] In some embodiments of the present invention, the lithium sodium alloy matrix has a sheet structure.

[0022] According to some preferred aspects of the present invention, the lithium-sodium alloy is rolled into the lithium-sodium alloy matrix by cold rolling.

[0023] Furthermore, in some preferred embodiments of the present invention, the cold rolling temperature is 20-35°C.

[0024] According to some preferred aspects of the present invention, during the cold rolling process, the deformation amount is controlled to be greater than 30%.

[0025] In some preferred embodiments of the present invention, during the cold rolling process, the deformation is controlled to be greater than 70% and the stress is not less than 1 GPa.

[0026] According to some preferred aspects of the present invention, the preparation method further comprises: contacting the lithium sodium alloy matrix with a sulfide solid electrolyte under pressure to generate a protective layer by reaction at the interface; wherein the mass percentage of sodium sulfide in the protective layer is more than 30%;

[0027] The sulfide solid electrolyte is removed.

[0028] In some embodiments of the present invention, the method of removing the sulfide solid electrolyte includes but is not limited to physical removal, scraping, or dissolution by chemical reaction, etc., which is not specifically limited here, as long as the lithium-sodium alloy negative electrode material can be obtained by splitting.

[0029] According to some preferred aspects of the present invention, the pressurization pressure of the pressurization condition is controlled to be 200-2000 MPa. Further, the pressurization time of the pressurization condition is controlled to be 1-600 min, for example, in some specific cases, it can be 3 min, 10 min, 15 min, 30 min, 50 min, 100 min, 200 min, etc.

[0030] In the present invention, since metallic sodium is more active than metallic lithium, when a lithium-sodium alloy matrix whose dominant crystal plane is (200) crystal plane is in contact with a sulfide electrolyte, it will spontaneously react to generate a layer of sodium sulfide on the surface. At the same time, a small amount of other reactants such as lithium sulfide, sodium phosphide, and sodium chloride may also be generated on the surface. Since there may still be trace amounts of oxygen in the environment, and lithium sodium has extremely high reducibility and is easy to react with oxygen, the alloy may also contain trace amounts of oxygen elements.

[0031] In some embodiments of the present invention, the direction of the pressurization is perpendicular to the plane where the interface is located.

[0032] In some embodiments of the present invention, the sulfide solid electrolyte may be a solid electrolyte material containing sulfur, specifically including but not limited to a lithium phosphorus sulfur chlorine solid electrolyte and / or a lithium silicon phosphorus sulfur chlorine solid electrolyte.

[0033] Another technical solution provided by the present invention is: an application of a lithium-sodium alloy negative electrode material in the preparation of an all-solid-state battery, wherein the all-solid-state battery uses a sulfide solid electrolyte as a solid electrolyte material, and in particular, the lithium-sodium alloy negative electrode material is prepared using the above-mentioned lithium-sodium alloy negative electrode material or using the above-mentioned method for preparing the lithium-sodium alloy negative electrode material.

[0034] Another technical solution provided by the present invention is a battery assembly, wherein the preparation method of the battery assembly comprises:

[0035] The lithium-sodium alloy is made into a lithium-sodium alloy matrix whose dominant crystal plane is the (200) crystal plane; wherein, in terms of mass percentage, sodium accounts for 65%-99% and lithium accounts for 1%-35% of the lithium-sodium alloy;

[0036] Under pressurized conditions, the lithium-sodium alloy matrix and the sulfide solid electrolyte are stacked, and a protective layer is generated by reaction at the interface where the lithium-sodium alloy matrix and the sulfide solid electrolyte are stacked and contacted. The mass percentage of sodium sulfide in the protective layer is more than 30%. After the reaction, a layered body is obtained, and the layered body serves as the battery component.

[0037] Another technical solution provided by the present invention is: an application of the battery assembly described above in the preparation of an all-solid-state battery.

[0038] In some embodiments of the present invention, the all-solid-state battery includes a lithium-ion battery, a sodium-ion battery, a sodium-sulfur battery, or the like.

[0039] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:

[0040] The inventors of the present invention are based on the problem that existing negative electrode materials are difficult to achieve high energy density, low cost, excellent cycle stability and other properties in lithium batteries with sulfide solid electrolytes with high ionic conductivity. During a large number of practical research processes, they unexpectedly discovered that when a lithium-sodium alloy matrix with a specific lithium-sodium ratio and a dominant crystal plane of (200) is used as the negative electrode of a lithium battery, it not only inhibits the growth of lithium dendrites, significantly increases the stability of the alloy negative electrode in the lithium-ion battery cycle, but also has a very high capacity density.

[0041] After a lot of experimental research and analysis, the inventors believe that the above effects can be achieved because, on the one hand, the dominant crystal plane is the (200) crystal plane, and lithium atoms can be embedded in the sodium unit cell to form a stable and uniform single phase. This structure is conducive to the subsequent practical application in lithium batteries. On the other hand, when the specific lithium-sodium alloy negative electrode material of the present invention is used as a negative electrode, it can react with the sulfur in the sulfide solid electrolyte to generate a stable sulfide (mainly sodium sulfide), which can form a stable protective layer on the surface of the negative electrode. This structure not only ensures the stability of the negative electrode material to the sulfide electrolyte, but also has an electronic band gap inside, which can effectively inhibit the transport of electrons at the interface, thereby effectively inhibiting the growth of lithium dendrites and greatly improving the cycle stability of the lithium battery.

[0042] In addition, in the negative electrode material of the present invention, since sodium is in the same family as lithium and has a smaller density, the negative electrode material is lighter in weight per unit volume, and the potential of the lithium-sodium alloy negative electrode provided by the present invention is almost the same as that of pure lithium; in particular, the negative electrode material of the present invention does not require the use of high atomic number precious metals, which greatly reduces costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0044] Figure 1 1 is an X-ray diffraction measurement diagram of pure lithium, pure sodium, and a lithium-sodium alloy matrix prepared at different feed ratios of lithium and sodium in an embodiment of the present invention; wherein, from top to bottom, they are respectively: pure lithium, pure sodium, a mass ratio of lithium metal to sodium metal of 0.01:0.99, a mass ratio of lithium metal to sodium metal of 0.1:0.9, a mass ratio of lithium metal to sodium metal of 0.3:0.7, and a mass ratio of lithium metal to sodium metal of 0.8:0.2;

[0045] Figure 2 for Figure 1 A partial enlarged view of the

[0046] Figure 3 Schematic diagram of a lithium-sodium alloy matrix having a (200) crystal plane as a dominant crystal plane in contact with a sulfide solid electrolyte in an embodiment of the present invention;

[0047] Figure 4 This is an impedance spectrum test diagram of a battery made using the battery assembly prepared in Application Example 2;

[0048] Figure 5 This is an impedance spectrum test diagram of a battery made using the pure lithium negative electrode of Comparative Example 1;

[0049] Figure 6This is a test diagram of the cycle performance of a battery made using the battery assembly prepared in Application Example 2;

[0050] Figure 7 A cycle performance test diagram of a battery made using the battery assembly prepared in Comparative Example 1;

[0051] Figure 8 This is a test diagram of the cycle performance of a battery made using the pure lithium negative electrode of Comparative Example 2. DETAILED DESCRIPTION

[0052] The above scheme is further described below in conjunction with specific embodiments; it should be understood that these embodiments are used to illustrate the basic principles, main features and advantages of the present invention, and the present invention is not limited to the scope of the following embodiments; the implementation conditions adopted in the embodiments can be further adjusted according to specific requirements, and the implementation conditions not specified are usually the conditions in conventional experiments.

[0053] Unless otherwise specified in the following examples, all raw materials are commercially available or prepared by conventional methods in the art.

[0054] Embodiment 1:

[0055] This example provides a lithium-sodium alloy negative electrode material and a preparation method thereof, and the preparation method of the lithium-sodium alloy negative electrode material comprises:

[0056] At 350°C, lithium metal and sodium metal (the mass ratio of lithium metal to sodium metal is 0.01:0.99) are melted and mixed to form a solid solution lithium-sodium alloy. The solid solution lithium-sodium alloy is cooled to room temperature and rolled into a lithium-sodium alloy matrix with a dominant crystal plane of (200) by cold rolling (rolling temperature 25°C, control of deformation during cold rolling to exceed 80%, and stress greater than 1.3 GPa). The lithium-sodium alloy matrix with a dominant crystal plane of (200) is used as a lithium-sodium alloy negative electrode material with a thickness of about 120 μm.

[0057] Embodiment 2:

[0058] This example provides a lithium-sodium alloy negative electrode material and a preparation method thereof, and the preparation method of the lithium-sodium alloy negative electrode material comprises:

[0059] At 350°C, lithium metal and sodium metal (the mass ratio of lithium metal to sodium metal is 0.1:0.9) are melted and mixed to form a solid solution lithium-sodium alloy. The solid solution lithium-sodium alloy is cooled to room temperature and rolled into a lithium-sodium alloy matrix with a dominant crystal plane of (200) by cold rolling (rolling temperature 25°C, control of deformation amount during cold rolling to exceed 80%, and stress greater than 1.3 GPa). The lithium-sodium alloy matrix with a dominant crystal plane of (200) is used as a lithium-sodium alloy negative electrode material with a thickness of about 120 μm.

[0060] Embodiment 3:

[0061] This example provides a lithium-sodium alloy negative electrode material and a preparation method thereof, and the preparation method of the lithium-sodium alloy negative electrode material comprises:

[0062] At 350°C, lithium metal and sodium metal (the mass ratio of lithium metal to sodium metal is 0.3:0.7) are melted and mixed to form a solid solution lithium-sodium alloy. The solid solution lithium-sodium alloy is cooled to room temperature and rolled into a lithium-sodium alloy matrix with a dominant crystal plane of (200) by cold rolling (rolling temperature 25°C, control of deformation during cold rolling to exceed 80%, and stress greater than 1.3 GPa). The lithium-sodium alloy matrix with a dominant crystal plane of (200) is used as a lithium-sodium alloy negative electrode material with a thickness of about 120 μm.

[0063] Comparative Example 1:

[0064] At 350°C, lithium metal and sodium metal (the mass ratio of lithium metal to sodium metal is 0.8:0.2) are melted and mixed to form a solid solution lithium-sodium alloy. The solid solution lithium-sodium alloy is cooled to room temperature and rolled into a lithium-sodium alloy matrix with a thickness of about 120 μm by cold rolling (rolling temperature 25°C, control of deformation amount during cold rolling to exceed 80%, and stress greater than 1.3 GPa). The dominant crystal plane is (110) crystal plane, which is used as a negative electrode material.

[0065] Comparative Example 2:

[0066] Pure lithium with a thickness of about 120μm is used as the negative electrode material.

[0067] The lithium sodium alloy negative electrode material of the present invention can be used in lithium batteries with sulfide solid electrolytes with high ionic conductivity, and solves the problem that existing negative electrode materials are difficult to have high energy density, low cost, excellent cycle stability and other performances. Further, based on the lithium sodium alloy negative electrode material of the present invention, it can react with the sulfide solid electrolyte, and some of the lithium and sodium therein respectively form stable chemical bonds with sulfur, generating a protective layer that is mainly sodium sulfide (and may also include lithium sulfide, etc.) for the sulfide solid electrolyte. After the reaction, in essence, the sulfide solid electrolyte can be removed without removing it, and the sulfide solid electrolyte used in the reaction process can be directly used as the solid electrolyte material of the battery, so it can be directly used in the battery in the form of their combination. The battery assembly composed of a lithium sodium alloy negative electrode material and a sulfide solid electrolyte and its preparation process are provided below, and some battery performance tests are performed on this basis.

[0068] Application Example 1:

[0069] This example provides a battery assembly and a method for preparing the same. The method for preparing the battery assembly includes:

[0070] At 350° C., lithium metal and sodium metal (mass ratio of lithium metal to sodium metal is 0.01:0.99) are melted and mixed to form a solid solution lithium sodium alloy, the solid solution lithium sodium alloy is cooled to room temperature, and the solid solution lithium sodium alloy (thickness is about 1000 μm) is rolled into a lithium sodium alloy matrix with a dominant crystal plane of (200) crystal plane and a thickness of about 120 μm by cold rolling (rolling temperature is 25° C., deformation amount of the cold rolling process is controlled to exceed 80%, and stress is greater than 1.3 GPa);

[0071] Under pressurized conditions, a lithium-sodium alloy matrix is ​​brought into contact with a lithium-phosphorus-sulfur-chlorine solid electrolyte in a stacked manner, and a reaction occurs at the interface where the lithium-sodium alloy matrix and the sulfide solid electrolyte are in stacked contact. After the reaction, a layered body is obtained, and the layered body is used as a battery component; wherein the pressurized pressure is 600 MPa, the pressurized time is 60 min, and the pressurized pressure direction is perpendicular to the plane where the interface is located.

[0072] Application Example 2:

[0073] This example provides a battery assembly and a method for preparing the same. The method for preparing the battery assembly includes:

[0074] At 350° C., lithium metal and sodium metal (mass ratio of lithium metal to sodium metal is 0.1:0.9) are melted and mixed to form a solid solution lithium sodium alloy, the solid solution lithium sodium alloy is cooled to room temperature, and the solid solution lithium sodium alloy (thickness is about 1000 μm) is rolled into a lithium sodium alloy matrix having a dominant crystal plane of (200) crystal plane and a thickness of about 120 μm by cold rolling (rolling temperature is 25° C., deformation amount of the cold rolling process is controlled to exceed 80%, and stress is greater than 1.3 GPa);

[0075] Under pressure, the lithium sodium alloy matrix is ​​in contact with the lithium phosphorus sulfur chlorine solid electrolyte (see the contact diagram for details). Figure 3 As shown), a reaction occurs at the interface where the lithium-sodium alloy matrix and the sulfide solid electrolyte are in stacked contact. After the reaction, a layered body is obtained, and the layered body is used as a battery component; wherein the pressurizing pressure is 600MPa, the pressurizing time is 60min, and the pressurizing pressure direction is perpendicular to the plane where the interface is located.

[0076] Application Example 3:

[0077] This example provides a battery assembly and a method for preparing the same. The method for preparing the battery assembly includes:

[0078] At 350° C., lithium metal and sodium metal (mass ratio of lithium metal to sodium metal is 0.3:0.7) are melted and mixed to form a solid solution lithium sodium alloy, the solid solution lithium sodium alloy is cooled to room temperature, and the solid solution lithium sodium alloy (thickness is about 1000 μm) is rolled into a lithium sodium alloy matrix having a dominant crystal plane of (200) crystal plane and a thickness of about 120 μm by cold rolling (rolling temperature is 25° C., deformation amount of the cold rolling process is controlled to exceed 80%, and stress is greater than 1.3 GPa);

[0079] Under pressurized conditions, a lithium-sodium alloy matrix is ​​brought into contact with a lithium-phosphorus-sulfur-chlorine solid electrolyte in a stacked manner, and a reaction occurs at the interface where the lithium-sodium alloy matrix and the sulfide solid electrolyte are in stacked contact. After the reaction, a layered body is obtained, and the layered body is used as a battery component; wherein the pressurized pressure is 600 MPa, the pressurized time is 60 min, and the pressurized pressure direction is perpendicular to the plane where the interface is located.

[0080] Application Comparative Example 1:

[0081] This example provides a battery assembly and a preparation method thereof, the preparation method of the battery assembly comprising: melting lithium metal and sodium metal (the mass ratio of lithium metal to sodium metal is 0.8:0.2) at 350°C, mixing to form a solid solution lithium sodium alloy, cooling the solid solution lithium sodium alloy to room temperature, and rolling the solid solution lithium sodium alloy (thickness is about 1000 μm) into a lithium sodium alloy matrix with a thickness of about 120 μm by cold rolling (rolling temperature is 25°C, the deformation amount of the cold rolling process is controlled to exceed 80%, and the stress is greater than 1.3 GPa), wherein the dominant crystal plane is the (110) crystal plane;

[0082] Under pressurized conditions, a lithium-sodium alloy matrix is ​​brought into contact with a lithium-phosphorus-sulfur-chlorine solid electrolyte in a stacked manner, and a reaction occurs at the interface where the lithium-sodium alloy matrix and the sulfide solid electrolyte are in stacked contact. After the reaction, a layered body is obtained, and the layered body is used as a battery component; wherein the pressurized pressure is 600 MPa, the pressurized time is 60 min, and the pressurized pressure direction is perpendicular to the plane where the interface is located.

[0083] Experimental test:

[0084] (1) XRD test was performed on the negative electrode materials obtained in Examples 1-3 and Comparative Example 1, as well as pure sodium and pure lithium in Comparative Example 2, and the following results were obtained: Figure 1-2 The XRD diffraction measurement spectrum shown, Figure 2 for Figure 1 A magnified view of a part in the middle;

[0085] Depend on Figure 1 and Figure 2 It can be seen that, unlike pure sodium, the (200) crystal plane in the negative electrode material of the present invention becomes the dominant crystal plane of the lithium-sodium alloy, and the lithium atoms are embedded in the sodium unit cell to form a stable and uniform single phase, so no characteristic peak of lithium is found in the X-ray diffraction measurement spectrum. Figure 2 It can be seen that the peak position of the sodium characteristic peak in the lithium-sodium alloy negative electrode material is shifted to the left compared with pure sodium, which proves the increase in the interplanar spacing and further indicates the insertion of lithium. The (200) crystal plane is a non-close-packed crystal plane of sodium metal with a large atomic gap. In addition, Figure 1 and Figure 2 It can be seen that when the mass ratio of lithium metal to sodium metal is 0.8:0.2 during preparation, the same cold rolling process is used, and the dominant crystal plane of the prepared lithium-sodium alloy matrix is ​​the (110) crystal plane.

[0086] (2) The battery assembly obtained in Example 2 was used to assemble a battery. The battery had a diameter of 1 cm, a positive electrode material of NCM811, a capacity of 4 mAh, a 30% lithium phosphorus sulfur chlorine electrolyte mixed in the positive electrode material, a total mass of the positive electrode part of about 25.9 mg, and an electrolyte film of lithium phosphorus sulfur chlorine electrolyte mixed with 5% PEO, with a density of 1.76 g / cm 3, the negative electrode weighs about 8 mg; when the electrolyte film thickness is less than 82 μm, the electrolyte film weighs about 10.8 mg, and the energy density of the whole battery can reach 350 Wh / kg, achieving the battery energy density industrialization target in 2025, of which the negative electrode mass accounts for about 17.8%.

[0087] (3) The battery assembly of Example 2 (the lithium sodium alloy matrix of Example 2 and the lithium phosphorus sulfur chlorine solid electrolyte are stacked and contacted, and the layered body obtained after the reaction) and the ternary metal oxide (NCM721) positive electrode are assembled into a full battery, and the change of its interface impedance under different cycle numbers is tested. The full battery assembled with the pure lithium negative electrode, lithium phosphorus sulfur chlorine solid electrolyte and ternary metal oxide (NCM721) positive electrode of Comparative Example 1 is selected as the control group. The test results are as follows: Figure 4 As shown, it can be seen that after ten cycles of the battery using the lithium sodium alloy negative electrode material of the present invention as the negative electrode, the interface impedance of the whole battery only increases by about 30Ω; while the pure lithium negative electrode under the same assembly test conditions, see Figure 5 As shown in FIG. 1 , the impedance increases by 400% in ten cycles. This result confirms that the lithium sodium alloy negative electrode material proposed in the present invention has good stability to sulfide electrolyte.

[0088] Furthermore, the battery assembled in the above manner was used to perform critical current density tests on the lithium sodium alloy negative electrode material of Example 2 of the present invention (a battery made by using the battery assembly prepared in Example 2), the negative electrode material obtained in Comparative Example 1 (a battery made by using the battery assembly prepared in Comparative Example 1), and the pure lithium negative electrode of Comparative Example 2 (a battery made by using the pure lithium negative electrode of Comparative Example 2, a lithium phosphorus sulfur chlorine solid electrolyte, and a ternary metal oxide (NCM721) positive electrode). The results are as follows: Figure 6-8 At room temperature, see Figure 6 As shown in Figure 2, the critical current density of the lithium-sodium alloy negative electrode material in Example 2 can exceed 6.34 mA·cm during the cycle test. -2 , see Figure 7 As shown in the figure, the critical current density of the negative electrode obtained in Comparative Example 1 during the cycle test was 0.51 mA·cm -2 When the short circuit failure occurs, that is, when the mass ratio of lithium metal and sodium metal exceeds the scope of the present invention, it is difficult to achieve a good application effect in the application; at the same time, refer to Figure 8 As shown, the current density of the pure lithium negative electrode of Comparative Example 2 during the cycle test is 0.45 mA cm -2 The above test results effectively confirm the inhibitory effect of the lithium sodium alloy negative electrode material proposed in the present invention on the growth of lithium dendrites.

[0089] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

[0090] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

Claims

1. A lithium-sodium alloy negative electrode material capable of inhibiting the growth of lithium dendrites, characterized in that: The lithium sodium alloy negative electrode material comprises a lithium sodium alloy matrix, wherein the dominant crystal plane of the lithium sodium alloy matrix is ​​a (200) crystal plane; Wherein, in the lithium-sodium alloy matrix whose dominant crystal plane is the (200) crystal plane, lithium atoms can be embedded in the sodium unit cell; In terms of mass percentage, in the lithium-sodium alloy negative electrode material, sodium accounts for 65%-99% and lithium accounts for 0.05%-34%; The lithium-sodium alloy matrix is ​​made of lithium-sodium alloy.

2. The lithium-sodium alloy negative electrode material capable of inhibiting lithium dendrite growth according to claim 1, characterized in that: The lithium sodium alloy matrix is ​​made by rolling the lithium sodium alloy.

3. The lithium-sodium alloy negative electrode material capable of inhibiting lithium dendrite growth according to claim 2, characterized in that: The rolling is cold rolling.

4. The lithium-sodium alloy negative electrode material capable of inhibiting lithium dendrite growth according to claim 2 or 3, characterized in that: During the rolling process, the deformation is controlled to be greater than 70% and the stress is not less than 1 GPa.

5. The lithium-sodium alloy negative electrode material capable of inhibiting lithium dendrite growth according to claim 4, characterized in that: During the rolling process, the deformation is controlled to be greater than 80% and the stress is greater than 1.3 GPa.

6. The lithium-sodium alloy negative electrode material capable of inhibiting lithium dendrite growth according to claim 2 or 3, characterized in that: The rolling is controlled to be carried out at 20-35°C.

7. The lithium-sodium alloy negative electrode material capable of inhibiting lithium dendrite growth according to claim 1, characterized in that: The lithium sodium alloy is prepared by the following method: melting lithium metal and sodium metal at 200-400° C., mixing to form a solid solution, and cooling.

8. The lithium-sodium alloy negative electrode material capable of inhibiting lithium dendrite growth according to claim 1 or 7, characterized in that: In terms of mass percentage, in the lithium-sodium alloy, sodium accounts for 65%-99% and lithium accounts for 1%-35%.

9. The lithium-sodium alloy negative electrode material capable of inhibiting lithium dendrite growth according to claim 1 or 7, characterized in that: The lithium sodium alloy matrix has a sheet-like structure.

10. The lithium-sodium alloy negative electrode material capable of inhibiting lithium dendrite growth according to claim 1, characterized in that: In terms of mass percentage, in the lithium-sodium alloy negative electrode material, sodium accounts for more than 70% and lithium accounts for less than 30%.

11. The lithium-sodium alloy negative electrode material capable of inhibiting lithium dendrite growth according to claim 10, characterized in that: In terms of mass percentage, in the lithium-sodium alloy negative electrode material, sodium accounts for 80%-95% and lithium accounts for 4%-19%.

12. The lithium-sodium alloy negative electrode material capable of inhibiting lithium dendrite growth according to claim 11, characterized in that: In terms of mass percentage, in the lithium-sodium alloy negative electrode material, sodium accounts for 85%-95% and lithium accounts for 4%-15%.

13. The lithium-sodium alloy negative electrode material capable of inhibiting lithium dendrite growth according to claim 1, characterized in that: The lithium sodium alloy negative electrode material also includes a protective layer formed on the lithium sodium alloy substrate; wherein the protective layer contains at least 30% by mass of sodium sulfide.

14. The lithium-sodium alloy negative electrode material capable of inhibiting lithium dendrite growth according to claim 13, characterized in that: The preparation method of the protective layer comprises: under pressure, bringing the lithium sodium alloy matrix into contact with a sulfide solid electrolyte, and reacting at the interface to generate a protective layer; wherein the mass percentage of sodium sulfide in the components of the protective layer is more than 30%.

15. The lithium-sodium alloy negative electrode material capable of inhibiting lithium dendrite growth according to claim 14, characterized in that: The method for preparing the protective layer further includes: removing the sulfide solid electrolyte after generating the protective layer.

16. The lithium-sodium alloy negative electrode material capable of inhibiting lithium dendrite growth according to claim 14, characterized in that: The pressurization pressure of the pressurization condition is controlled to be 200-2000 MPa, and the pressurization time of the pressurization condition is controlled to be 1-600 min; and / or, the pressurization pressure direction is perpendicular to the plane where the interface is located.

17. The lithium-sodium alloy negative electrode material capable of inhibiting lithium dendrite growth according to claim 14, characterized in that: The sulfide solid electrolyte is a lithium phosphorus sulfur chlorine solid electrolyte and / or a lithium silicon phosphorus sulfur chlorine solid electrolyte.

18. The lithium-sodium alloy negative electrode material capable of inhibiting lithium dendrite growth according to claim 13, characterized in that: In terms of mass percentage, sulfur accounts for 0.05%-2% in the lithium-sodium alloy negative electrode material.

19. The lithium-sodium alloy negative electrode material capable of inhibiting lithium dendrite growth according to claim 13, characterized in that: The lithium sodium alloy negative electrode material further comprises, in terms of mass percentage, 0.001%-0.5% phosphorus, 0.001%-0.5% chlorine and 0.001%-0.5% oxygen; The protective layer also contains lithium sulfide, sodium phosphide and sodium chloride.

20. Use of a lithium-sodium alloy negative electrode material capable of inhibiting the growth of lithium dendrites as claimed in any one of claims 1 to 19 in the preparation of an all-solid-state lithium battery.

21. The use according to claim 20, characterized in that The all-solid-state lithium battery uses a sulfide solid electrolyte as a solid electrolyte material.